Exploring purine analogues as inhibitors against Katanin, a microtubule severing enzyme using molecular modeling approach - Vibhuti Saxena; Pruthanka Patil; Purva Khodke; Bajarang Vasant Kumbhar (Scientific Reports)
Abstract Katanin, a key protein in cellular architecture, plays a crucial role in severing microtubules, which are vital components of the cytoskeleton. Given its central involvement in cell division and proliferation, katanin represents a promising target for therapeutic intervention, particularly in cancer treatment. Inhibiting katanin’s function could potentially hinder the uncontrolled growth of cancerous cells, making it an attractive target for novel anti-cancer therapies. Previous studies have shown that purine-based compounds exhibit a strong affinity for microtubule-severing enzymes. In this study, we aim to identify potential purine-type inhibitors of katanin using molecular modeling techniques. A total of 276,280 purine-type compounds from the PubChem database were subjected to structure-based high-throughput virtual screening, followed by ADME prediction, PASS analysis, and molecular docking studies. These efforts led to the identification of two potent compounds: PubChem CID 122589735 and 123629569, which demonstrated strong binding interactions with katanin. Molecular dynamics simulations further revealed that these compounds effectively altered katanin’s conformation when compared to ATP. Additionally, binding energy calculations indicated that PubChem CID 122589735 exhibited the strongest binding affinity for katanin, with the binding free energy ranking as follows: 122589735 > 123629569 > ATP. Our findings suggest that the screened compounds, particularly PubChem CID 122589735, hold promise as potential katanin inhibitor. These compounds could play a significant role in the development of new anti-cancer therapies targeting a variety of carcinoma. Future research, including in vitro and in vivo studies, is essential to assess the efficacy and safety of these inhibitors, paving the way for innovative cancer treatments.